Migraine in cervical artery dissection and ischemic stroke patients - Metso, Tiina M.; Grond-Ginsbach, Caspar; Kloss, Manja (Neurology, 2012)
Objective: Several small to medium-sized studies indicated a link between cervical artery dissection (CeAD) and migraine. Migrainous CeAD patients were suggested to have different clinical characteristics compared to nonmigraine CeAD patients. We tested these hypotheses in the large Cervical Artery Dissection and Ischemic Stroke Patients (CADISP) population. Methods: A total of 968 CeAD patients and 653 patients with an ischemic stroke of a cause other than CeAD (non-CeAD IS) were recruited. CeAD patients with stroke (CeADstroke, n ϭ 635) were compared with non-CeAD IS patients regarding migraine, clinical characteristics, and outcome. CeAD patients with and without migraine were compared in terms of clinical characteristics and outcome. Results: Migraine was more common among CeADstroke patients compared to non-CeAD IS patients (35.7 vs 27.4%, p ϭ 0.003). The difference was mainly due to migraine without aura (20.2 vs 11.2%, p Ͻ 0.001). There were no differences in prevalence of strokes, arterial distribution, or other clinical or prognostic features between migrainous and nonmigrainous CeAD patients. Conclusion: Migraine without aura is more common among CeADstroke patients compared to nonCeAD IS patients. The mechanisms and possible causative link remain to be proved. Although CeAD is often complicated by stroke, our data do not support increased risk of stroke in migrainous CeAD patients. Neurology® 2012;78:1221-1228